2014
DOI: 10.2147/cia.s53153
|View full text |Cite
|
Sign up to set email alerts
|

The role of gastrostomy tube placement in advanced dementia with dysphagia: a critical review

Abstract: PurposeOver 4.5 million people in North America had a diagnosis of dementia in the year 2000, and more than half had advanced disease with potential aspiration risk. There is much controversy regarding the use and timing of enteral feeding support in these patients with dysphagia. The management of dysphagia is far more complex when considering quality of life, “comfort care” hand feeding, the use of percutaneous endoscopic gastrostomy tube (PEG), and associated mortality rates. This study seeks to critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 12 publications
2
66
0
12
Order By: Relevance
“…The ability of our clinical interventions (dietary modification, NPO status, and/or gastrostomy tube placement) to reduce pneumonia incidence and mortality is relatively unknown . Recent reviews suggest that dietary modification and NPO status may have no effect on overall survival, and this is further supported by our dataset . A relatively high mortality risk of aspiration is demonstrated by our data, with an overall all‐cause 3‐year mortality rate of 39% for patients in our cohort with a PAS score of 5 or greater.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The ability of our clinical interventions (dietary modification, NPO status, and/or gastrostomy tube placement) to reduce pneumonia incidence and mortality is relatively unknown . Recent reviews suggest that dietary modification and NPO status may have no effect on overall survival, and this is further supported by our dataset . A relatively high mortality risk of aspiration is demonstrated by our data, with an overall all‐cause 3‐year mortality rate of 39% for patients in our cohort with a PAS score of 5 or greater.…”
Section: Discussionsupporting
confidence: 63%
“…Our data show that patients with deconditioning and generalized dysphagia due to frailty and dementia have substantially increased risk of pneumonia and overall mortality. Goldberg and Altman directly addressed this population in a systematic review of patients with dementia and showed no long‐term survival benefit of percutaneous endoscopic gastrostomy (PEG) placement for these patients . Early PEG placement may be indicated for these patients to maintain quality of life, hydration, nutrition, and ease of medication administration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was no difference between enteral tube insertion in an earlier or a later stage in the course of the disease in relation to survival outcome 64. Two recent reviews of observational studies also acknowledged the lack of evidence to suggest a positive correlation between enteral tube feeding and survival 65 66. The risks of enteral feeding in patients with advanced dementia are related to procedural complications, postinsertion tube management (eg, blockages and dislodgements) and the tendency of cognitively impaired patients to interfere with the tube (eg, by pulling the tube out) 59…”
Section: Enteral Feeding In Alzheimer's Disease and Other Dementiasmentioning
confidence: 99%
“…However, end‐stage dementia where someone is bed‐bound, at times with contractures, very limited or no vocabulary and experiencing episodes of aspiration or dehydration due to poor oral intake, indicates that many therapeutic options are futile. In this situation, there is no evidence to suggest that feeding tubes will improve longevity, cause weight gain or prevent aspiration or pressure sores 16 …”
Section: Considering Dementiamentioning
confidence: 99%